The Effect of Customer Engagement Social Media to Brand Loyalty Indosat Ooredoo - Lafi Afifah; Arianis Chan; Healthy Nirmalasari (Ekonomi Bisnis, 2020)
This research aims to study and determine about the condition of customer engagement social media, the condition of brand loyalty on Indosat Ooredoo and effects of customer engagement social media to brand loyalty on Indosat Ooredoo. The research method that used is descriptive research and the design of research is survey. The sampling technique that used is non-probability sampling and done by using purposive sampling with 300 respondents. Meanwhile, data analysis that used is simple linear regression-analysis, the coefficient of determination, and hypothesis testing.The result of this study shown the condition of customer engagement and brand loyalty on Indosat Ooredoo has been good. Furthermore, there is significant effect from customer engagement social media to brand loyalty on Indosat Ooredoo at medium level. It is mean every increasing  from customer engagement will impact to increasing on brand loyalty.